Gestión de publicidad en el Minimarket D’ Liss Aguilar de la parroquia San Juan durante el periodo 2023. - Arias Vinces, Angelica Kristel (2024)
During the 2023 period, the D'Liss Aguilar Minimarket in San Juan Parish implemented effective advertising management strategies to enhance its presence in the local market. In an increasingly competitive business environment, the minimarket stood out for its proactive approach to the promotion and visibility of its products and services. Advertising management focused on several key initiatives, including social media campaigns, point-of-sale promotions and collaborations with local businesses. Through an active presence on platforms such as Facebook and Instagram, the D'Liss Aguilar Minimarket managed to increase its follower base, interact with the community and disseminate information about offers and news. Point-of-sale promotions were strategically designed to incentivize impulse purchases and build customer loyalty. Discounts, special packages and rewards programs contributed to generating a greater flow of customers and consolidating the position of the minimarket as an attractive option for daily needs. Additionally, collaborations with local businesses allowed D'Liss Aguilar Minimarket to expand its reach and attract new customers through mutually beneficial partnerships. Joint events, sponsorships and participation in community activities reinforced the connection of the minimarket with the parish and generated a positive image in the minds of consumers.